Pengaruh Sosialisasi Perpajakan, Sanksi Pajak, Pelayanan Fiskus, Ajaran Tri-nga, dan Kesadaran Wajib Pajak Terhadap Kepatuhan Wajib Pajak Orang Pribadi - Intan, Seri; Mubarok, Abdulloh; Susetyo, Budi (Universitas 17 Agustus 1945 Jakarta, 2025)
This research aims to analyze the influence of tax socialization,tax penalties, tax authorities services, tri-nga teachings and taxpayer awareness on individual taxpayer compliance. Primary data collected through questionnaire with respondents are individual taxpayers at KPP Pratama Tegal, Tegal City in 2024. Tegal, Tegal City in 2024. By using random sampling technique, This study used 400 respondents as samples. By using SPSS version 22 software, this research uses quantitative research. The results of this study indicate that tax socialization,tax sanctions, fiscal services, tri-group teachings and taxpayer awareness have a positive effect on individual taxpayer compliance in the city of tegal. positive effect on compliance of individual taxpayers in tegal city. The implication of this research is that if we want to increase taxpayer compliance, then the priority order of strategies that can be carried out starts from improving tax services, increasing taxpayer awareness, improving Tri-nga teachings, increasing understanding of tax sanctions, and tax socialization activities